Experimental Study on Seismic Behavior of Precast Bolt-Connected Steel-Members End-Embedded Concrete (PBSEC) Beam-Column Connections - Zhun Wang; De-Cheng Feng; Gang Wu (Buildings, 2022)
With the rapid development and research of precast concrete frame structures, it is not difficult to find that the structural form and seismic performance of dry-connected precast joints have always been the focus of research. Since this type of structural system is complex, the construction is inconvenient in practical application, and many additional parts need to be installed, this paper develops a kind of precast bolt-connected steel-members end-embedded concrete (PBSEC) beam-column connection to solve the shortcomings of the current dry-connected precast joints. There is no wet work in the assembly process, and all-dry construction and assembly methods are used. There is no need to pour concrete and support formwork, which significantly improves construction efficiency compared to wet and cast-in-situ connections. Low cyclic reversed loading tests were conducted to obtain test data, such as failure mode, hysteresis curve, skeleton curve, stiffness, ductility, and deformation capacity of the precast concrete joint. The failure mode of the PBSEC joints is the buckling failure of the connecting steel plate, leading to a perfect seismic capacity and collapse resistance of the structure. The hysteresis curves of the PBSEC joints are bow-shaped and full in shape, showing high energy dissipation capacity. The bearing capacity of the joints begins to rise rapidly at the initial loading stage and then decreases slowly after reaching the peak, which is an ideal shape. By summarizing the average peak load, strength degradation coefficient, loop energy per cycle, loop energy per level, and cumulative energy damping coefficient, it is found that the joint using 10 mm thick Q235 steel can obtain the most suitable failure mode and obtain the best energy dissipation performance. When the strength of the steel plate material increases, the energy dissipation performance of the joint drops.